On Alexandrov lattices - Albert Gorelishvili (International Journal of Mathematics and Mathematical Sciences)
By an Alexandrov lattice we mean a δ normal lattice of subsets of an abstract set X, such that the set of ℒ-regular countably additive bounded measures is sequentially closed in the set of ℒ-regular finitely additive bounded measures on the algebra generated by ℒ with the weak topology.